2017
DOI: 10.18769/ijasos.367300
|View full text |Cite
|
Sign up to set email alerts
|

Tradition of Cynicism: From Origin to Nowadays

Abstract: Cynicism commonly is interpreted as a moral phenomenon. However this understanding of cynicism is not completed. It is necessary to analyze the tradition of cynicism as a philosophical and cultural phenomenon. The cynicism is especially popular during the periods of crisis, amid the breakdown of ideologies and religious doctrines. The tradition of cynicism is inseparable from the history of kynicism. Nowadays the phenomenon of cynicism is widely spread in the Western world. In accordance with the philosophy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Later on, it took a negative attitude which gave birth to the idea of absurdity. Kudriavtseva (2014) observed that three factors contributed to the negative interpretation that gave birth to the rise of cynicism. Firstly, the idea of the early cynics was misinterpreted because of their particular way of life; which led to the second reason; the popularity of pseudo-cynicism in ancient times which happens to be a perverted version of cynicism that promotes absurdity; Third, the name of the school had negative connotation.…”
Section: Points Out Several Ramifications Below;mentioning
confidence: 99%
See 1 more Smart Citation
“…Later on, it took a negative attitude which gave birth to the idea of absurdity. Kudriavtseva (2014) observed that three factors contributed to the negative interpretation that gave birth to the rise of cynicism. Firstly, the idea of the early cynics was misinterpreted because of their particular way of life; which led to the second reason; the popularity of pseudo-cynicism in ancient times which happens to be a perverted version of cynicism that promotes absurdity; Third, the name of the school had negative connotation.…”
Section: Points Out Several Ramifications Below;mentioning
confidence: 99%
“…By implication, modern man has an embattled consciousness where on one hand, enlightenment with its ideals of equality brotherhood, justice and a reasonable and meaningful life; on the other hand, the realization that we must live against these ideals and rules to feed and forces man to live the opposite of the rules. www.rsisinternational.org According to Kudriavtseva (2014), cynicism is a philosophy that originated in antiquity and borrows from the philosophical school of knyisism. He noted that cynicism is related to conflicts between ideologies.…”
Section: Points Out Several Ramifications Below;mentioning
confidence: 99%